A Wild Idea : How the Environmental Movement Tamed the Adirondacks - Edmondson, Brad (Book collections on Project MUSE., 2021)
"The history of a globally significant land-use plan for New York State's six-million-acre Adirondack Park, the environmentalists who worked for decades to turn it into law, and the opponents who rose to meet them"--